IDENTIFIKASI WASTE DI RUANG RAWAT JALAN DAN RAWAT INAP RUMAH SAKIT ISLAM SURABAYA - Puryanti Puryanti (UNUSA Press, 2018)
Hospitals as healthcare providers are demanded more competitive in the era of national healthinsurance. Therefore the hospital faces the challenges of improving the quality of health services byusing available resources. The study aims to to identify waste in outpatient and inpatient rooms ofSurabaya Islamic Hospital. The descriptive study involved 90 patients from outpatient and inpatientrooms. The study found waste by defect category, waiting time, non utilize talent, transportation,inventory, motion, and extra processing based on business process analysis. Category of waste overproduction not found. The causes of the occurrence of waste most comes from the man, material, andmethod factors. Program recommendations include scheduling patient-based arrival of servicegroup, visite scheduling and polyclinic service and temporary payment method change, for inpatientprogram program consisting of 5R program implementation, rearranging standard operatingprocedure of patient's diet information, improvement of prescribing system for patient and standardoperating procedure rearrangement return of insurance patients.